Perencanaan bak kontrol dalam pengendalian sedimentasi pada saluran drainase STA 18+850 sampai dengan 19+325 jalan poros Samarinda-Bontang - Farisca Sasti Gadis Setiawan; Ezra Hartarto Pongtuluran; Mariatul Kiptiah (Civil Engineering Dept, Balikpapan State Polytechnics, 2024)
Arterial road Samarinda-Bontang often experiences flooding due to the accumulation of sediment in the channels, leading to a reduction in their capacity. This study aims to determine the erosion rate that will occur around the channels, the sedimentation rate that will occur in the channels, and to design the necessary dimensions for a control structure in the channels. The analysis and calculations were conducted using the Universal Soil Loss Equation (USLE) method to estimate the sedimentation volume for the next 10 years. The calculations were carried out using Microsoft Excel software, carefully following appropriate steps, resulting in the sedimentation volume figure used for the design of the control structure. From the analysis, it was found that the rainfall erosivity factor (R) is 13,588.02 Ton.mm/year, the soil erodibility factor (K) is 0.08, the length and slope factor (LS) is 3.68, and the Sediment Delivery Ratio (SDR), which represents the average proportion of sediment transported to the channel to the total erosion in the river basin, is 0.0941. These values yielded a potential erosion rate of 2,837.96 Ton/km²/year, an actual erosion rate of 1,557.002 Ton/km²/year, and a potential sedimentation rate of 146.5529 Ton/km²/year. Based on these values, the projected sedimentation volume in the channels over a 10-year period is 556.81 m³. Therefore, a control structure with dimensions of 20m in length, 2m in width, and 13.92m in depth, or alternatively 20m in length, 2m in width, and 1.39m in depth, is required for a planning period of 1 year.